Informal carer role in the personalization of assistive solutions connected to aspirations of people with dementia - De Filippis, Maria Laura; Craven, Michael P.; Dening, Tom (Springer Verlag, 2014)
The increase in the elderly population over the last thirty years with consequent increase in the number of people living with dementia (PwD) has resulted in a research focus on improving quality-of-life and well-being beyond basic needs, to address psychosocial needs and to provide technological support for these. As part of a UK industry-led, publically supported, project Connect-ing Assistive Solutions to Aspirations (CASA), research is being conducted to inform the design of assistive technology packages that are aspiration-led. Focus groups were conducted with informal carers (family relatives) of persons with dementia to elicit views on technology use for increasing independence of PwD (with a carer living at home). The focus groups were analysed through thematic analysis and the results have been used to produce personas and scenarios for creation of demonstrator assisted living packages.